Eptacog Beta for Bleeding Treatment and Prevention in Congenital Hemophilia A and B With Inhibitors: A Review of Clinical Data and Implications for Clinical Practice. Issue 7 (July 2022) - Ciolek, Alana M.; Arnall, Justin; Moore, Donald C.; Palkimas, Surabhi; Der-Nigoghossian, Julie; Dane, Kathryn
Objective: To review the pharmacology, dosing and administration, safety, clinical efficacy, and role of eptacog beta in the treatment of congenital hemophilia with inhibitors. Data Sources: A literature search of PubMed (1966 to August 2021) was conducted using the keywords eptacog beta, recombinant FVII, and hemophilia . Study Selection and Data Extraction: All relevant published articles and prescribing information on eptacog beta for the treatment of congenital hemophilia with inhibitors were reviewed. Data Synthesis: Eptacog beta is a novel recombinant activated factor VII (rVIIa) product that demonstrated efficacy in controlling bleeding and associated pain in patients with hemophilia A or B with inhibitors. Eptacog beta has limited Food and Drug Administration–approved and off-label indications compared with other bypassing agents (BPAs; activated prothrombin complex concentrates [aPCC; eptacog alfa]). Eptacog beta costs less than eptacog alfa, but still more than aPCCs. Relevance to Patient Care and Clinical Practice: This review provides insight into the role of eptacog beta for treatment of congenital hemophilia with inhibitors and reviews important health system formulary considerations for available BPAs. Conclusions: Eptacog beta is more cost-effective than eptacog alfa and, as such, may become the preferred rVIIa formulary product. However, eptacog alfa availability remains necessary for the treatment of disorders where eptacog beta has limited data. aPCC should remain the first-line BPA for the treatment of bleeding in patients with inhibitors with no contraindications to use because of its equivocal efficacy and safety and in light of the magnitude of cost savings associated with this strategy.